Development of computer ethical framework for information security (educational context) - Namayander, Meysam (2009)
Information security and ethics have viewed as one of the foremost areas of concern and interest by academic researchers and industry practitioners. They are defined as an all-encompassing term that refers to all activities needed to secure information and systems that supports it in order to facilitate its ethical use. In this research, this very important part of current studies introduced and the fundamental concepts of a security framework are discussed. To achieve the goals of information security and ethics in Malaysian setting, there is a need of proper research and Malaysian students at Universiti Teknologi Malaysia International Campus Kuala Lumpur are chosen as a case study. Many kinds of technology-induced issues involve economic, political, social, operational and others. However, the most important and controversial issues often deals with such legal and ethical matters as security and privacy from educational aspects. Using survey research, insight is provided regarding the extent to which and how university student have dealt with issues of computer ethics and results of designed information security and computer ethics framework on their future career and behavioral experience are addressed.